ANALISA KINERJA KEUANGAN PEMERINTAHKABUPATEN LAMONGAN TAHUN ANGGARAN 2009-2013 - RIZKA HENDYTA, AMANDA (Jurnal Akuntansi AKUNESA, 2015)
This research aimed to analyze the financial performance of Lamongan District fiscal year 2009-2013. This research method using descriptive method with secondary data. To measure the performance of this government to use some ratios, including independence ratio, the dependency ratio, the ratio of fiscal decentralization, effectiveness ratio, efficiency ratio, and the ratio of revenue growth. Results of the research showed that the ratio of 10.96% which means the independence of Lamongan district quite independent in funding through the regional interest revenue received. Lamongan District dependency ratio 2009-2013 fiscal year showed an average of 75.22%, which means "Very High". The ratio of fiscal decentralization Lamongan in fiscal year 2009-2013 showed an average 7.61%, which means "Very Less". Effectiveness ratio of regional income have a tendency "Highly Effective" with a 113.4% rate of effectiveness. Efficiency ratio Lamongan 2009-2013 income have a tendency "Less Efficient", with a rate of 94.71% efisiesi. PAD growth but growth slowed from 2010 to 2011. While in 2013 decreased 4.66%.Keyword : Lamongan District, measurement of financial working performance, regional financial ratio.